Errors in Learning Japanese through Listening-Misheard Cases- - Hermawan, Gede Satya (Universitas Pendidikan Indonesia (Indonesia University of Education), 2019)
This paper aims to study the error that happens when students learning Japanese through listening. This paper describes misheard cases by students during listening class. The data in this research collected from students’ quiz and test results. Students participated in this study were first-year and second-year students, including 37 first-years students and 24 second-year students, with total participants 81 students. The data collected in this study then categorized based on the type of errors. The results showed that the errors occurred include confusion between two sounds, reduction of sound, and mis-guessing long vowel. Confusing of two sounds happened when the students misheard two different sounds such as alveolar nasal consonant /n/ in [hinan] with liquid consonant /r/ as in [hiran]. Furthermore, reduction of sound is occurred when students confused the same vowel at particle with front or back vowel sound of the word, such as yamagaafureru which misheard with yamagafureru. This error occurred because the vowel sound /a/ on particle /ga/ which covering up the vowel sound /a/ in the front of the word afureru. Lastly, there are errors that happened because thin overlapping borderline between error or mistake, where students mostly misheard or mistaken short vowels sound such as [ba∫o] with long vowels such as [ba∫o:].